A View from Addis Ababa: From “1989” to Today’s Revolutions in Africa - Engel, Ulf (Comparativ, 2019)
This article looks at responses over time by the OAU and its successor, the African Union, to popular uprisings and revolutions in member states. With a focus on the critical junctures of 1989, 2011, and 2019, the article concludes that these changes were mainly dealt with against the backdrop of continental experiences, but rarely situated in a global context.